2021
DOI: 10.1186/s13195-020-00751-x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the QPLEX™ Alz plus assay, a novel multiplex kit for screening cerebral amyloid deposition

Abstract: Background Alzheimer’s disease (AD) is an irreversible neurodegenerative disease characterized by the hallmark finding of cerebral amyloid deposition. Many researchers have tried to predict the existence of cerebral amyloid deposition by using easily accessible blood plasma samples, but the effectiveness of such strategies remains controversial. Methods We developed a new multiplex kit, the QPLEX™ Alz plus assay kit, which uses proteomics-based blo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…We previously reported that our QPLEX TM biomarkers (Aβ1–40, POSTN, LGALS3BP, and ACE) showed significant differences between age-matched (age >55 years old) PiB − and PiB + participants (Fig. 1a ) 21 . In this study, we utilized biomarkers to determine whether amyloid accumulated within the CN group (CN − , n = 185, PiB-PET negative; CN + , n = 36, PiB-PET positive; Table 1 ) (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…We previously reported that our QPLEX TM biomarkers (Aβ1–40, POSTN, LGALS3BP, and ACE) showed significant differences between age-matched (age >55 years old) PiB − and PiB + participants (Fig. 1a ) 21 . In this study, we utilized biomarkers to determine whether amyloid accumulated within the CN group (CN − , n = 185, PiB-PET negative; CN + , n = 36, PiB-PET positive; Table 1 ) (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Previously, we identified blood biomarkers that can differentiate those with from those without cerebral amyloid deposition and suggested the possible relevance of these biomarkers in AD diagnosis 11 . Based on these blood biomarkers, the QPLEX TM Alz plus assay kit was developed, and the efficiency of its diagnostic performance was assessed by clinically applying it to a large population cohort >55 years of age involving CN, MCI, and AD groups 21 . In the present study, we focused on QPLEX TM biomarkers in CN individuals across a broad age range, including CN individuals <55 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations